2016
DOI: 10.1108/scm-12-2015-0467
|View full text |Cite
|
Sign up to set email alerts
|

Managing reverse exchanges in service supply chains

Abstract: UWE makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited. UWE makes no representation that the use of the materials will not infringe any patent, copyright, trademark or other property or proprietary rights. UWE accepts no liability for any infringement of intellectual property rights in any material deposited but will remove such material from public view pending investigation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…This result supports the theoretical benefits pointed on several studies regarding the importance of accuracy and availability of real time information and the operations transactions along forward and reverse movement of physical goods in both services and manufacturing industry (Sun, 2012;Ting et al, 2010;Xu et al, 2012;Reaidy et al, 2014;Kumar et al, 2016). The second top ranked benefit was the improvement in products tracking and traceability (mean = 4.34), a crucial element within services and manufacturing operations to achieve efficiency enhancements in productivity through synchronized flow of material and information (Costa et al, 2012;Cao et al, 2013;Uddin and Sharif, 2016).…”
Section: Benefits To Individual Organizationssupporting
confidence: 76%
“…This result supports the theoretical benefits pointed on several studies regarding the importance of accuracy and availability of real time information and the operations transactions along forward and reverse movement of physical goods in both services and manufacturing industry (Sun, 2012;Ting et al, 2010;Xu et al, 2012;Reaidy et al, 2014;Kumar et al, 2016). The second top ranked benefit was the improvement in products tracking and traceability (mean = 4.34), a crucial element within services and manufacturing operations to achieve efficiency enhancements in productivity through synchronized flow of material and information (Costa et al, 2012;Cao et al, 2013;Uddin and Sharif, 2016).…”
Section: Benefits To Individual Organizationssupporting
confidence: 76%
“…Successful management of the reverse supply chain is one way to improve customer perception and loyalty [70][71][72]. It can also play a large part in the pro tability of opportunistic 3 rd party remanufacturers [73].…”
Section: The Reverse-logistics Networkmentioning
confidence: 99%
“…Consequently, in considering these elements, the study investigates the area of RE and healthcare, a progressive area of research suggested by Kumar et al (2016) and Esain et al (2016). Practical issues with the implementation of the RE initiative are considered, a suggestion supported by Filho (2012, 2016).…”
Section: Legal Statutes Affecting Reusementioning
confidence: 99%